Exploring long-term global environmental impacts of chlorinated paraffins (CPs) in waste: Implications for the Stockholm and Basel Conventions and the global plastic treaty - J. Chen; S. Zhang; Xu, W.; C. Chen; Chen, A.; R. Lu; Q Jing; J Liu* (Environment International, 2024)
Chlorinated paraffins (CPs), mainly short-chain CPs (SCCPs) and medium-chain CPs (MCCPs), are currently the most produced and used industrial chemicals related to persistent organic pollutants (POPs) globally. These chemicals are widely detected in the environment and in the human body. As the release of SCCPs and MCCPs from products represents only a small fraction of their stock in products, the potential long-term release of CPs from a large variety of products at the waste stage has become an issue of great concern. The results of this study showed that, by 2050, SCCPs and MCCPs used between 2000 and 2021 will cumulatively generate 226.49 Mt of CP-containing wastes, comprising 8610.13 kt of SCCPs and MCCPs. Approximately 79.72 Mt of CP-containing wastes is predicted to be generated abroad through the international trade of products using SCCPs and MCCPs. The magnitude, distribution, and growth of CP-containing wastes subject to environmentally sound disposal will depend largely on the relevant provisions of the Stockholm and Basel Conventions and the forthcoming global plastic treaty. According to multiple scenarios synthesizing the provisions of the three conventions, 26.6–101.1 Mt of CP-containing wastes will be subject to environmentally sound disposal as POP wastes, which would pose a great challenge to the waste disposal capacity of China, as well as for countries importing CP-containing products. The additional 5-year exemption period for MCCPs is expected to see an additional 10 Mt of CP-containing wastes subject to environmentally sound disposal. Thus, there is an urgent need to strengthen the Stockholm and Basel Conventions and the global plastic treaty.